Blood profile of Tilapia (Oreochromis niloticus) fed fortification feed with seaweed flour (Gracilaria sp.) - Linda Linda; Dewi Nur'aeni Setyowati; Dewi Putri Lestari (Universitas Muhammadiyah Malang, 2022)
Seaweed Gracilaria sp. is a marine plant that contains secondary metabolites that can be used as an immunostimulant in tilapia (Oreochromis niloticus). The blood picture can be used as an evaluation material for the physiological response of fish. The aim of the study was to determine the effect of fortification of seaweed flour Gracilaria sp. on the blood profile of tilapia. The study used an experimental method with 4 treatments, namely, P1: control feed; P2: flour fortification of Gracilaria sp. 4%; P3: 8%; and P4: 12% respectively. The research data were analyzed by linear regression for the blood profile and variance for the absolute weight, SR, and FCR data. The results showed that fortification of seaweed flour Gracilaria sp. the feed did not have a significant effect on hemoglobin levels, hematocrit, erythrocyte counts, and leukocytes. However, it has a significant effect on increasing absolute weight, survival, and feed conversion rates. Flour fortification of Gracilaria sp. with a concentration of 8% or 80g/kg of feed is the best concentration that can affect the blood profile